Health utility and survival after hospital admission with acute cardiogenic pulmonary oedema. Issue 6 (4th October 2010) - Goodacre, Steve; Gray, Alasdair; Newby, David; Dixon, Simon; Masson, Moyra; Sampson, Fiona; Nicholl, Jon; Elliot, Mark; Crane, Steven
Abstract : Background: The aim of this study was to measure health utility and survival in patients with acute cardiogenic pulmonary oedema (ACPO), identify predictors of outcome and determine the effect of initial treatment with non-invasive ventilation (NIV) upon outcomes. Methods: A randomised controlled trial was conducted at 26 hospitals in the UK. 1069 adults with ACPO were randomised to continuous positive airway pressure (CPAP), non-invasive positive pressure ventilation (NIPPV) or standard oxygen therapy. The main outcome measures were survival to 1–5 years, health utility measured using the EQ-5D survey at 1, 3 and 6 months, and quality-adjusted life years (QALYs). Results: Median survival was 771 days (95% CI 669 to 875), with no difference between the three treatment groups (p=0.827). Age (HR 1.042, 95% CI 1.031 to 1.052), chronic obstructive pulmonary disease (HR 1.13, 95% CI 1.06 to 1.62), cerebrovascular disease (HR 1.41, 95% CI 1.14 to 1.73) and diabetes mellitus (HR 1.31, 95% CI 1.01 to 1.63) independently predicted mortality. Mean EQ-5D scores were 0.578, 0.576 and 0.582 at 1, 3 and 6 months, respectively, with no significant difference between the treatment groups. Male gender (+0.045 QALYs, 95% CI 0.009 to 0.081) and cerebrovascular disease (−0.080 QALYs, 95% CI −0.131 to −0.029) independently predicted health utility. Conclusion: Patients with ACPO have high mortality and reduced health utility. Initial treatment with CPAP or NIPPV does not alter subsequent survival or health utility.